KEARIFAN LOKAL SEBAGAI UPAYA KONSERVASI MATA AIR MUDAL DI DESA BULU KECAMATAN BULU KABUPATEN REMBANG - Venny Amalia; Tjaturahono Budi Sanjoto; Puji Hardati (STKIP Singkawang, 2023)
The Mudal Spring is the main source of clean water for the people of Bulu Village, Bulu District, Rembang Regency and is also used to meet the needs of people outside the village which is managed by the Regional Drinking Water Company (PDAM). The increasing demand for clean water, the conservation of sustainable water resources is necessary. The purpose of this study was to analyze the condition of the Mudal springs and the household clean water needs of Bulu Village residents and to analyze the role of local wisdom as an effort to conserve springs. The research was conducted by observing in the field the condition of the springs used for household water supply, interviews related to household clean water needs and the local wisdom of the Bulu Village community which acts as an effort to conserve springs. A number of respondents using springs and local community leaders who live near the springs were interviewed freely and in a structured manner to obtain data on the use of springs and local wisdom in spring conservation which is still being carried out today. The results showed that the results of the water sample from the Mudal spring met water quality standards which included physical, chemical, and bacteriological parameters with the amount of clean water needed in Bulu Village of 136 liters/person/day, this indicates that the total water needs of the villagers Feathers are larger than the water requirement according to SNI, which is 100 liters/person/day. The large need for clean water requires spring conservation efforts for the sustainability of water resources for the future. As well as using the local wisdom of Bulu Village which is manifested in the form of a tradition of community service to clean springs and alms of the earth (slametan) by the local community led by village elders.